A case report of palmar xanthoma with xanthomatous neuropathy - Hyun Yi Lee; Dae Won Koo; Joong Sun Lee (SAGE Open Medical Case Reports, 2021)
Xanthomas are plaques or nodules consisting of an accumulation of excess lipids, resulting in the formation of foam cells in the skin or tendons. Typically, xanthomas are not accompanied by other symptoms. Here, we report a patient with a presentation of painful palmar xanthomas and subsequent diagnosis of metabolic and cardiovascular morbidities. A 44-year-old man presented with multiple yellowish, firm, and painful nodules on his right palm and fingers. Lipid panel and medical examination revealed a diagnosis of type III hyperlipoproteinemia and diabetes mellitus type II. Histopathological examination of the lesions revealed numerous lipid-laden foamy cells surrounding the nerve bundles through the dermis. This unique presentation of painful xanthomas prior to the manifestation of more significant underlying conditions suggested that xanthomas might be used as early diagnostic indicators. Based on this case, we propose more thorough examinations of palmar xanthomas in patients for earlier detection of potentially lethal diseases.